Effect of Magnetic Storm Related Thermospheric Changes on the Evolution of Equatorial Plasma Bubbles. Issue 3 (25th March 2019) - Bhattacharyya, A.; Fedrizzi, M.; Fuller‐Rowell, T. J.; Gurram, P.; Kakad, B.; Sripathi, S.; Sunda, S.
Abstract: Past efforts to predict scintillations on VHF and L‐band radio signals recorded at equatorial and low‐latitude stations have been mostly based on a theoretical linear growth rate of Rayleigh‐Taylor instability on the bottomside of the post‐sunset equatorial F layer, which is responsible for the generation of an equatorial plasma bubble (EPB). However, it is the maximum height that an EPB reaches above the dip equator and development of intermediate scale irregularities within the EPB, in its nonlinear phase of evolution that determines the latitudinal distribution of scintillations. Amplitude scintillations recorded by a network of VHF and L‐band receivers on a quiet day, 13 March 2015 and on 20 March 2015, a few days after the 17 March 2015 magnetic storm, show that latitudinal extent of scintillations caused by EPB irregularities is lesser on 20 March than on 13 March. Geomagnetic and ionosonde data from an equatorial station, and vertical total electron content distributions obtained from Global Navigation Satellite Systems observations, indicate that the equatorial ionospheric conditions are approximately same on these 2 days. Simulation of thermospheric conditions for these 2 days is carried out using the Coupled Thermosphere, Ionosphere, Plasmasphere, and Electrodynamics model. It is found that thermospheric atomic oxygen density is enhanced in the aftermath of the major magnetic storm of 17 March 2015, resulting in enhanced ion‐neutral collision frequencies over the dip equator on 20 March. This limits the height to which an EPB rises over the dip equator on this day, and thus impacts the latitudinal distribution of scintillations. Key Points: Two days with similar heights of post‐sunset equatorial F layer base have different latitudinal distributions of VHF and L‐band scintillations Estimated densities of thermospheric O on these 2 days using CTIPe model show enhancement on the day preceded by a magnetic storm Enhanced ion‐neutral collision frequency on this day limits vertical extent of EPB, which impacts latitudinal distribution of scintillations